Virus inoculation in mice bearing Ehrlich ascitic tumors: antigen production and tumor regression. - Mettler, N E (1982)
Ehrlich ascitic carcinoma, as developed in albino mice, has been used as a source of hemagglutinating and complement-fixing antigens, and it proved to be suitable for one type of antigen, or both, for at least 12 viruses of 16 tested. Hemagglutinins were obtained with members of arbovirus groups A, B, and C; complement-fixing antigens were obtained for at least one member of each antigenic group tested. Ehrlich ascitic tumor was compared with sarcoma 180 as a source of antigens; although sarcoma 180 showed many advantages over Ehrlich tumor, the latter gave, in general, better results for complement-fixing antigens. Oncolytic effect with complete recovery of the mice was observed in some instances. The highest recovery rate resulted with Congo and UNA viruses (40%), and the second highest rate resulted with dengue 2, St. Louis, Hazara, and Uukuniemi viruses (20%). The best survival was observed, in decreasing order, with Congo, St. Louis, dengue 2, Tacaribe, Sindbis, Junin, and Amapari viruses.